An experimental strength of coach peel rivets joining similar and dissimilar sheet materials - Rohani, Daud (2008)
The multi-materials structure has been applied as one of the methods in weight reduction especially in automotive industry. In this thesis, tensile test were performed in order to analyze the strength of similar and dissimilar sheet material joins connected rivets. It is used aluminum and steel sheet materials. Besides that, it is to study the fundamental phenomenon of tensile strength acted on coach peel riveted joints under similar and dissimilar sheet materials. Both materials are combined together to obtain the best comprise between weight reduction and the strength of the structure. The specimens of riveted joining was evaluated with tensile test in order to find the elastic of modulus (E), ultimate strength (σut), yield strength (σy), proportional limit (σpl) and the fracture point (εf) from stress-strain diagram. The tensile strength for similar specimens is 22.25 MPa. While for the dissimilar sheet materials is 22.20 MPa. The percentage of difference between both specimens is very small, 0.22%.